The relationship between job burnout and some demographic characteristics among nurses of AJA hospitals in Tehran - Z farsi; E afaghi (فصلنامه ابن سینا)
Background: Job burnout is a significant problem in the staff of health organizations, particularly nurses, and leads to more clinical errors, patients' dissatisfaction, job leave, and negative outcomes which will eventually lead to lack of human force. Given the nature of nursing and its key role in looking after patients, this study aims to investigate the relationship between job burnout and some demographic characteristics of nurses working in AJA hospitals in Tehran.